2018
DOI: 10.1017/ice.2018.259
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Staphylococcus aureus infections in patients admitted to freestanding pediatric hospitals, 2009–2016

Abstract: We observed pediatric S. aureus hospitalizations decreased 36% from 26.3 to 16.8 infections per 1,000 admissions from 2009 to 2016, with methicillin-resistant S. aureus (MRSA) decreasing by 52% and methicillin-susceptible S. aureus decreasing by 17%, among 39 pediatric hospitals. Similar decreases were observed for days of therapy of anti-MRSA antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The stability in methicillin resistance among S. aureus cultures of community-onset infections differs from other epidemiologic studies that have reported decreases in methicillin resistance in pediatric S. aureus infections. [4][5][6] Most prior studies analyzed trends in hospitalized children, which may account for this difference and would align with our finding of MSSA predominance in invasive infections. The cause of national increases in invasive MSSA is unclear.…”
Section: Discussionsupporting
confidence: 85%
“…The stability in methicillin resistance among S. aureus cultures of community-onset infections differs from other epidemiologic studies that have reported decreases in methicillin resistance in pediatric S. aureus infections. [4][5][6] Most prior studies analyzed trends in hospitalized children, which may account for this difference and would align with our finding of MSSA predominance in invasive infections. The cause of national increases in invasive MSSA is unclear.…”
Section: Discussionsupporting
confidence: 85%
“…The difference in the colonization rate may be attributed to the different study locations or periods. In the United States, a decline in the proportion of MRSA among S. aureus isolates (60.4% decrease) or a trend of MRSA infection (52% decrease) has been observed in the pediatric population since 2010 ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, complicated skin and soft tissue infections (cSSTIs) and bacteremia due to Staphylococcus aureus are common causes of infection for children, and although infection rates have declined, methicillinresistant S. aureus (MRSA) remains a threat worldwide [1][2][3][4][5]. Methicillin-resistant strains continue to cause a large proportion of cSSTIs and bloodstream infections (bacteremia) caused by S. aureus [4].…”
Section: Introductionmentioning
confidence: 99%